Hubungan Motivasi Belajar dengan Komunikasi Pembelajaran Sistem E-Learning pada Mahasiswa PGSD di Masa Pandemi Covid-19 - Anang Fathoni; Ali Mustadi; Wahyu Kurniawati (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This research aimed to determine the motivation of learning, communication of e-learning system, and relationship motivation learning and communication learning system of students of primary teacher Education, University PGRI Yogyakarta at the Covid-19 pandemic. This research used quantitative approaches with associative methods. The location of this research at PGRI University Yogyakarta with respondents amounted to 159 students of 2nd semester, consisting of 25 male students and 134 female students. The collection of research data used a questionnaire with a Likert rating scale. Analysis of data by using the correlation formula of product-moment from Pearson with the help of SPSS version 23 of Windows. The results of the study showed that motivational learning data gained good criteria with an average of 2.77, e-learning system learning communication data obtained good criteria with an average value of 2.77, and there was a significant relationship (0.822) between learning motivation with learning communication system e-Learning in the Covid-19 pandemic. This shows that the higher the motivation to learn the higher the learning of E-Learning system communication. Abstrak: Penelitian ini bertujuan untuk mengetahui motivasi belajar, komunikasi pembelajaran sistem E-Learning, dan hubungan motivasi belajar dan komunikasi pembelajaran sistem E-Learning mahasiswa PGSD Universitas PGRI Yogyakarta pada masa pandemi Covid-19. Penelitian ini menggunakan pendekatan kuantitatif dengan metode asosiatif. Lokasi penelitian ini di Universitas PGRI Yogyakarta dengan responden berjumlah 159 mahasiswa PGSD semester II, yang terdiri dari 25 mahasiswa laki-laki dan 134 mahasiswa perempuan. Pengumpulan data penelitian menggunakan angket dengan skala Likert. Analisis data dengan menggunakan rumus korelasi product moment dari Pearson dengan bantuan SPSS versi 23 windows. Hasil penelitian menunjukkan data motivasi belajar memperoleh kriteria baik dengan rata-rata 2,77, data komunikasi pembelajaran sistem E-Learning memperoleh kriteria baik dengan nilai rata-rata 2,77, dan terdapat hubungan yang signifikan (0,822) antara motivasi belajar dengan komunikasi pembelajaran sistem E-Learning di masa pandemi Covid 19. Hal ini menunjukkan bahwa semakin tinggi motivasi belajar maka semakin tinggi pula komunikasi pembelajaran sistem E-Learning.